2017
DOI: 10.1080/19434472.2017.1373690
|View full text |Cite
|
Sign up to set email alerts
|

Between a rock and a hard place of geopolitically sensitive threats – critical incidents and decision inertia

Abstract: Between a rock and a hard place of geopolitically sensitive threats -critical incidents and decision inertia http://researchonline.ljmu.ac.uk/id/eprint/7193/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. AbstractThis paper analyses the management of high-profile geopolitically sensitive threats (verifying potential terrorist identity, hostage rescue and national/international security). Defining features of such cases include decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Least-worst decisions require the decision-maker to take decisive action and overcome fear, doubt, and uncertainty to commit to a least-worst choice (Alison et al, 2018;Shortland et al, 2019). However, research has indicated that the process of least-worst decision-making can often become derailed, resulting in decision inertia.…”
Section: Introductionmentioning
confidence: 99%
“…Least-worst decisions require the decision-maker to take decisive action and overcome fear, doubt, and uncertainty to commit to a least-worst choice (Alison et al, 2018;Shortland et al, 2019). However, research has indicated that the process of least-worst decision-making can often become derailed, resulting in decision inertia.…”
Section: Introductionmentioning
confidence: 99%
“…Further, and even more demanding, is the fact that the decision-maker considers that all anticipated outcomes appear equally aversive (or that choosing between the least-worst quickly is very difficult). Examples of least-worst decisions range from emergency responses such as the California Wildfire response, or Grenfell Tower in London, to international crises such as the Syrian Civil war ( Alison et al, 2018 ). What all of these decisions have in common is the lack of “good” options, a need to make a decision within a given (and often short) timeframe, and significant personal, political, and societal consequences.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, least-worst decision-making is often shown to become de-railed, resulting in decision inertia. Decision inertia involves the delaying of the decision-making process through either avoidance, redundant deliberation, or failure to implement a decision ( Alison et al, 2018 ). In many applied situations the failure to make a decision in time (or at all), is as damaging, if not worse, than an incorrect decision ( Shortland et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This realization appears to be in direct conflict with the core purpose of the CCS, as the lessons learnt only serve to remind multi-agency systems and individual response agencies of their potentially transgressive actions. In other words, lesson learned do not necessarily translate to effective future decision-making, as decisions are often found to be made in context to an incident (Rebera and Rafalowski, 2014), as agencies focus toward least-worst decisions, rather than optimal outcomes (Alison et al, 2018). The reformation of centralized governing bodies highlights insufficiencies of UK government emergency response management structures (Kapucu, 2009).…”
Section: Sub-level Narrativesmentioning
confidence: 99%